Comparison between dressing of cellulitis with normal saline and Magnesium sulphate - Singh, Rita; Sreenivasa, P. (International Surgery Journal, 2018)
Background: Cellulitis is an acute inflammatory condition of the skin that is characterized by localized pain, erythema, swelling and heat. Cellulitis may be caused by indigenous flora colonies of the skin appendages. Methods: This study comprises of patients attending MNR Medical College and Hospital between February 2015 to January 2018. After proper history taking, examination and investigations patients were admitted or treated as out-patients. Results: Patients treated with normal saline dressing responded better than Magnesium sulfate dressing. No complication was observed, and healing was faster. Conclusions: In this study, author have observed patients treated with normal saline dressing responded better than Magnesium sulfate dressing. No complication was observed, and healing was faster.